Inferring Methane Production by Decomposing Tree, Shrub, and Grass Leaf Litter in Bog and Rich Fen Peatlands - Yavitt, Joseph B.; Kryczka, Anna K.; Huber, Molly E.; Pipes, Gwendolyn T.; Rodriguez, Alex M. (Frontiers in Environmental Science, 2019)
Plant litter provides a fresh source of energy and nutrients to fuel microbial activity in soil, and in northern peatlands this can be leaf litter from mosses, graminoids, shrubs, and / or trees. Because Sphagnum and other mosses decompose slowly, vascular plant litter assumes a principal role, but its role in microbial methane production is unclear. Therefore, we examined decomposition of leaf litter from nine species, including trees, shrubs, and graminoids, using litterbags positioned for up to 2.5 years in two raised bogs and in two rich fens. Across species leaf litter quality varied for concentrations of nitrogen, soluble organic matter, and cell wall composition. After 2.5 years of decay the amount of leaf litter mass remaining ranged from 43 to 63% in the bogs versus 17 to 71% in the rich fens. Thus, site conditions interacted with litter quality to determine decay rates but with idiosyncratic patterns. Leaf mass remaining after 0.5, 1.5 and 2.5 years of decay was incubated in vitro, without soil, to assess its ability to support methane production and concomitant anaerobic carbon dioxide respiration. Residue from all nine species supported methane production, with the greatest rates (up to 5000 nmol g-1 day-1) in tissue with high concentrations of pectin. Rates were 2- to 700-times greater for the leaf material that decomposed in the rich fens than in the bogs. Production rates were more variable for methane than for anaerobic respiration. As seen for mass loss, differences in litter quality predicted variation in gas production rates but differently in the bogs than in the rich fens. The results underscore the importance of vascular plant litter in the biogeochemistry of carbon and methane in peatlands and why vegetation, plant species composition, and peatland type must be described to put peatland ecosystems into global budgets of carbon and methane.